e-HRM: Changes in Business and Labor Culture in the Digital Paradigm - Faroman Syarief; Hepsi Nindiasari; Martanto Martanto; Budi Febriani; Riyanto Wujarso (Universitas Dharma Wacana, 2022)
This article reviews electronic Human Resource Management (e-HRM) and the economy's changing business and workforce culture according to the digital paradigm. Based on the definitions and initial framework, the review analyzes the theory used. In diagnosing the ongoing transition to changing work relationships and business culture in the digital age, the study reveals an initial collection of work from a variety of disciplines, the majority of which employ diverse empirical methods and draw from various levels of analysis and e-HRM focus topics. This study employs a qualitative approach and descriptive methodologies. The study's findings indicate that e-HRM offers significant advantages for organizational success, particularly in terms of work efficiency and effectiveness. E-HRM is intended for workers outside the HR department, as well as employees and organizational management. E-HRM enables HR applications to be accessed by personnel outside of the firm at any time and from any location. E-HRM is a transformation in an organization's business and worker culture. These changes include business process activities, workforce planning, recruitment, employee/payroll/employee leave information systems, evaluation and remuneration, performance and training, and employee development.